Factors Affecting the Success of Accrual-Based Accounting Implementation in the Sidoarjo Regency Government - Rizky Eka Tamara; Sarwenda Biduri (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the factors that influence the success of the implementation of accrual-based accounting in the Sidoarjo Regency Government (Study on the Sidoarjo Regency Government). The sampling method used is the Slovin formula. The sample in this study amounted to 114 samples. The data used is primary data. The data analysis method used in this study is Multiple Linear Regression with SPSS 23. The results of this study indicate that human resource expertise has an effect on the success of accrual-based accounting implementation in the Sidoarjo Regency Government. The quality of technology and information systems affect the success of the implementation of accrual-based accounting in the Sidoarjo Regency Government. Organizational commitment affects the success of accrual-based accounting implementation in the Sidoarjo Regency Government. Organizational culture influences the success of accrual-based accounting implementation in the Sidoarjo Regency Government.